Promoting the rule of law abroad : in search of knowledge - Carothers, Thomas, 1956- (Carnegie Endowment for International Peace, 2006)
"Over the past decade, Carothers has established himself as the leading U.S. expert on democracy promotion. He is a powerful critic not only of the nuts-and-bolts of democracy assistance but also of U.S. grand strategy overall."--SAIS Review Promoting the rule of law has become a major part of Western efforts to spread democracy and market economics around the world. Yet, although programs to foster the rule of law abroad have mushroomed, well-grounded knowledge about what factors ensure success, and why, remains scarce. In Promoting the Rule of Law Abroad, leading practitioners and policy-oriented scholars draw on years of experience-in Russia, China, Latin America, Central and Eastern Europe, the Middle East, and Africa-to critically assess the rationale, methods, and goals of rule-of-law policies. These incisive, accessible essays offer vivid portrayals and penetrating analyses of the challenges that define this vital but surprisingly little-understood field. Contributors include Rachel Belton (Truman National Security Project), Lisa Bhansali (World Bank), Christina Biebesheimer (World Bank), Thomas Carothers (Carnegie Endowment), Wade Channell, Stephen Golub, and David Mednicoff (University of Massachusetts, Amherst), Laure-HElEne Piron (Overseas Development Institute), Matthew Spence (Yale Law School), Matthew Stephenson (Harvard Law School), and Frank Upham (NYU School of Law)